The use of IVF/ICSI and risk of postpartum hemorrhage: A retrospective cohort study of 153,765 women in China - Tang, Di; Cheng, Yufeng; Feng, Xiaosheng; Li, Xiaocui; Coyte, Peter C. (Frontiers in Public Health, 2023)
Objective: Postpartum hemorrhage (PPH) is the leading cause of maternal morbidity and mortality. Identifying women who are at high risk of PPH is crucial for implementing early preventive and interventive strategies. This study aimed to examine whether there is an association between the use of in vitro fertilization (IVF) /intracytoplasmic sperm injection (ICSI) and increased risk of PPH. Method: This retrospective cohort study was conducted using medical record data from women who delivered at a tertiary hospital in Shanghai, China, between January 1, 2013 and April 30, 2019. Logistic regression analysis was used to estimate the associations between the use of IVF/ICSI and the risk of PPH. Results: A total of 153,765 pregnant women were included, of which 6484 conceived through IVF/ICSI and147,281 conceived naturally. The incidence of PPH was 1.9% in this cohort. The incidence of PPH in women who conceived through IVF/ICSI was significantly higher than those in women who conceived naturally (3.4% vs 1.7%, p < 0.01). The use of IVF/ICSI was associated with an increase in the amount of postpartum blood loss. Compared to women who conceived naturally, the average amount of postpartum blood loss increased by 42.1 ml (β=42.1, 95% CI, 38.2-46.0) for women who conceived through IVF/ICSI. In addition, women who conceived through IVF/ICSI were at higher risk of maternal PPH. The adjusted odds ratio (OR) of PPH in women who conceived through ART was 2.7 (OR=2.7, 95% CI, 2.3-3.1). Conclusion: Our findings demonstrated that women who conceived through IVF/ICSI were at higher risk of PPH and suggested to obstetricians and midwives to identify and implement early preventative strategies for PPH among pregnant women who conceived through IVF/ICSI.